No evidence of a curvilinear relation between conscientiousness and relationship, work, and health outcomes - Nickel, Lauren B. (2021)
Across 2 studies and 4 samples (Ns = 8,332, 2,136, 4,963, and 753, respectively), we tested whether the relation between conscientiousness and variables associated with important aspects of individuals’ lives were curvilinear such that being high on conscientiousness was manifestly negative. Across multiple outcomes including measures of health, well-being, relationship satisfaction, job satisfaction, and organizational citizenship, we found no evidence for a systematic curvilinear relation between conscientiousness and these outcomes. Furthermore, heeding the call to use more sophisticated psychometric modeling of the conscientiousness spectrum, we used different types of scale construction and scoring methods (i.e., dominance and ideal point) and again found no evidence of curvilinear relationships between conscientiousness and the aforementioned variables. We discuss the potential reasons for the inconsistency with past research.